O padrão de comunicação na área de administração: o caso brasileiro e o caso americano - Russo, Mariza (1991)
Communication patterns of scientists in the Business Administration area as represented by two relevant journals in the field: the Revista de Administração de Empresas, published by the University of São Paulo, and the Harvard Business Review, published by the Harvard Business School. Bibliometric laws were used for evaluation purposes as well as citation analysis of references included in papers published during the period analyzed (1986-1988). Finding indicated that, in spite of similar physical features, the two journals differ, since one is a scientific and the other is a technical journal. The majority of authors in both journals belong to the academic community, and prefer to write papers as single authors. They tend to cite journals in which they publish, and have high number of self citations. Among other results, the study that the American academic community is more "self centered" than the Brazilian, since there is a higher rate of self citations in the Harvard Business Review than in the Revista de Administração. Other evidences found in this research also support this conclusion.